2021
DOI: 10.1021/acs.inorgchem.1c00886
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterizations of a Plutonium(III) Crown Ether Inclusion Complex

Abstract: We report the synthesis, single-crystal structure, solid-state ultraviolet−visible−nearinfrared spectroscopy, and theoretical calculations on the first trivalent plutonium crown ether inclusion complex, [(H 3 O)(18-crown-6)][Pu(H 2 O) 4 (18-crown-6)](ClO 4 ) 4 •2(H 2 O) (denoted as Pu III -18C6). Single-crystal X-ray diffraction reveals that Pu III -18C6 crystallizes in the orthorhombic space group of Pccn, which is assembled by independent ionic pairs including [Pu(H 2 O) 4 (18-crown-6)] 3+ , [(H 3 O)(18-crow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The spectra of Nd1, Nd2, and solution of Nd2 in DMSO (Figure 2) contain G 9/2 , 4 G 7/2 ; 2 K 13/2 , 2 G 7/2 , 4 G 5/2 ; 4 S 3/2 , 4 F 7/2 ; 2 H 9/2 , 4 F 5/2 ; and 4 F 3/2 , and are similar to those for previously reported Nd III coordination compounds. 61,62 The spectra of solid-state of Pu1, Pu2, and a DMSO solution phase of Pu2 show the typical Laporte-forbidden 5f → 5f transitions of Pu III from the predominantly 6 64 As shown in Figure 3, other high-intensity 5f → 5f transitions, group H ( 6 F 11/2 ), group F ( 6 H 15/2 , 6 F 9/2 ), group E ( 6 H 13/2 ), group D ( 6 F 7/2 ), group C ( 6 H 11/2 ), and group B ( 6 F 3/2 , 6 H 5/2 , 6 H 9/2 ), for Pu(III) can be observed in absorbance spectrum of solid-state of Pu1, Pu2 and a DMSO solution phase of Pu2. It should be noted these line groups for energylevel assignments are based on the calculated in thin films of LaCl 3 :Pu by Carnall and co-workers.…”
Section: Synthesis Of {[Pu(pmtzmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra of Nd1, Nd2, and solution of Nd2 in DMSO (Figure 2) contain G 9/2 , 4 G 7/2 ; 2 K 13/2 , 2 G 7/2 , 4 G 5/2 ; 4 S 3/2 , 4 F 7/2 ; 2 H 9/2 , 4 F 5/2 ; and 4 F 3/2 , and are similar to those for previously reported Nd III coordination compounds. 61,62 The spectra of solid-state of Pu1, Pu2, and a DMSO solution phase of Pu2 show the typical Laporte-forbidden 5f → 5f transitions of Pu III from the predominantly 6 64 As shown in Figure 3, other high-intensity 5f → 5f transitions, group H ( 6 F 11/2 ), group F ( 6 H 15/2 , 6 F 9/2 ), group E ( 6 H 13/2 ), group D ( 6 F 7/2 ), group C ( 6 H 11/2 ), and group B ( 6 F 3/2 , 6 H 5/2 , 6 H 9/2 ), for Pu(III) can be observed in absorbance spectrum of solid-state of Pu1, Pu2 and a DMSO solution phase of Pu2. It should be noted these line groups for energylevel assignments are based on the calculated in thin films of LaCl 3 :Pu by Carnall and co-workers.…”
Section: Synthesis Of {[Pu(pmtzmentioning
confidence: 99%
“…Among the more exciting developments of the past decade of actinide chemistry has been an expansion of our understanding of the nature of chemical bonding in this series. The more radially extended Frontier orbitals of actinides compared with those of lanthanides can lead to the formation of partially covalent bonds with a variety of ligands. When this is combined with the pronounced relativistic effects present in the 5f series, deviation from analogous 4f elements is often noted. , As a consequence of this, An III cations can exhibit larger bond enthalpies to coordinating ligands than measured with Ln III cations .…”
Section: Introductionmentioning
confidence: 99%
“…The favourable cytotoxicity of metal complexes containing dithiocarbamate ligands can be coupled to the ion-encapsulating capabilities of crown ether moieties to come up with synergistic complexes with enhanced anticancer profiles. 68,[284][285][286][287][288] The similarity of crown ether ligands to natural ionophores such as gramicidin (10), valinomycin (11) and nonactin (12), on the fact that they possess a hydrophilic cavity with a hydrophobic periphery, suggests that they might be a good option to transport ions across cell membranes. 289,290 There are reports on functionalized crown ether-DTC compounds capable to bind and cleave DNA.…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%
“…For realization of the latter approach, we synthesized an 18-crown-6-based organic linker, 4,4′-(2,3,5,6,8,9,11,12,14,15-decahydrobenzo­[ b ]­[1,4,7,10,13,16]­hexaoxacycloocta-decine-17,20-diyl)­dibenzoic acid (H 2 TPDC-18C6; Figure ), containing terminal carboxylate groups required for postsynthetic installation. For instance, a molecular 18-crown-6-based complex, [(H 3 O)­(18C6)]­[Pu­(H 2 O) 4 (18C6)]­(ClO 4 ) 4 ·2H 2 O (18C6 = 1,4,7,10,13,16-hexaoxacyclooctadecane), previously showed that the crown ether fragment, 18C6, can chelate radionuclides, such as plutonium . Using the same crown ether moiety, 18C6, we were able to achieve metal coordination with cerium cations (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a molecular 18-crown- radionuclides, such as plutonium. 48 Using the same crown ether moiety, 18C6, we were able to achieve metal coordination with cerium cations (Figure S1). 49 Selection of the H 2 TPDC-18C6 linker, possessing a 15.6 Å length along the three-phenyl backbone, was dictated by geometrical constraints, i.e., the size of the pocket between metal nodes (16 Å) in the parent PCN-700 framework, as described below (Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%